High genetic diversity in geographically remote populations of endemic and widespread coral reef angelfishes (genus: Centropyge) - Hobbs, Jean-Paul; Van Herwerden, L.; Jerry, D.; Jones, G.; Munday, P. (Blackwell Science Ltd, 2013)
In the terrestrial environment, endemic species and isolated populations of widespread species have the highest rates of extinction partly due to their low genetic diversity. To determine if this pattern holds in the marine environment, we examined genetic diversity in endemiccoral reef angelfishes and isolated populations of widespread species. Specifically, this study tested the prediction that angelfish (genus: Centropyge) populations at Christmas and CocosIslands have low genetic diversity. Analyses of a 436 base pair fragment of the mtDNA control region revealed that the endemic C. joculator exhibited high haplotype (h > 0.98 at both locations) and nucleotide (Christmas pi% = 3.63, Cocos pi% = 9.99) diversity. Similarly, isolated populations of widespread angelfishes (C. bispinosa and C. flavicauda) had high haplotype (h > 0.98) and nucleotide (pi% = 2.81 and pi% = 5.78%, respectively) diversity. Therefore, in contrast to terrestrial patterns, endemic and isolated populations of widespread angelfishes do not have low genetic diversity, rather their haplotype and nucleotide diversities were among the highest reported for marine fishes. High genetic diversity should reduce extinction risk in these species as itcould provide the evolutionary potential to adapt to the rapidly changing environmental conditions forecast for coral reefs